Relationship between enamel mechanical, chemical, ultrastructural properties and mammalian bite force (2021)
Mammalian enamel is one of the hardest and most mineralized tissues in the body. Its main function is to support the loads generated during the chewing process. Mechanical, chemical and ultrastructural properties are responsible for providing it with the high resistance necessary to withstand constant loads and for making the animal’s tooth functional through its life. Animal bite forces as well as their feeding patterns can influence enamel ultrastructure, improving its behavior when facing chewing loads. A brief review of enamel mechanical and chemical properties as well as a brief review on mammalian enamel decussation characteristics are presented in chapter 2. The methodology used in this study is shown in chapter 3, experimental results in terms of mechanical, chemical and ultrastructural properties are presented in chapter 4. In Chapter 5 the results of the experimentation are analyzed in terms of their statistical correlations and the relationship between enamel properties, bite force, and feeding patterns of the analyzed specimens. Finally the conclusions of this investigation are shown in chapter 6. The bite force of the analyzed animals (BFQ) is related to the elastic modulus of the enamel and that the enamel of the analyzed species shows similar characteristics to human enamel in terms of the variations in mechanical and chemical properties. The properties analyzed were compared in terms of the taxonomic classification or the feeding patterns of the analyzed specimens. The mechanical variables (elastic modulus and hardness) do not seem to be related to taxonomic classification or feeding patterns. The decussation fraction is greater than 0:8 regardless of the taxonomic classification or feeding patterns, enamel thickness and decussated thickness are statistically correlated with decussated band thickness, this could indicate that these variables are important in delaying crack growth. Ultrastructural variables do not seem to depend on taxonomic classification or feeding patterns.